First demonstration of in vivo mapping for regional brain monoacylglycerol lipase using PET with [(11)C]SAR127303 - Yamasaki, Tomoteru (Neuroimage, 2018)
Monoacylglycerol lipase (MAGL) is a main regulator of the endocannabinoid system within the central nervous system (CNS). Recently, [(11)C]SAR127303 was developed as a promising radioligand for MAGL imaging. In this study, we aimed to quantify regional MAGL concentrations in the rat brain using positron emission tomography (PET) with [(11)C]SAR127303. An irreversible two-tissue compartment model (2-TCMi, k(4) = 0) analysis was conducted to estimate quantitative parameters (k(3), K(i)(2-TCMi), and λk(3)). These parameters were successfully obtained with high identifiability (< 10 %COV) for the following regions ranked in order from highest to lowest: cingulate cortex > striatum > hippocampus > thalamus > cerebellum > hypothalamus ≈ pons. In vitro autoradiographs using [(11)C]SAR127303 showed a heterogeneous distribution of radioactivity, as seen in the PET images. The K(i)(2-TCMi) and λk(3) values correlated relatively highly with in vitro binding (r > 0.4, P < 0.005). The K(i)(2-TCMi) values showed high correlation and low underestimation (< 10%) compared with the slope of a Patlak plot analysis with linear regression (K(i)(Patlak)). In conclusion, we successfully estimated regional net uptake value of [(11)C]SAR127303 reflecting MAGL concentrations in rat brain regions for the first time.